Hypoxia sensing and responses in Parkinson’s disease - Burtscher, Johannes; Duderstadt, Yves; Gatterer, Hannes; Burtscher, Martin; Vozdek, Roman; Millet, Grégoire; Hicks, Andrew A.; Ehrenreich, Hannelore; Kopp, Martin (International journal of molecular sciences, 2024)
Parkinson’s disease (PD) is associated with various deficits in sensing and responding to reductions in oxygen availability (hypoxia). Here we summarize the evidence pointing to a central role of hypoxia in PD, discuss the relation of hypoxia and oxygen dependence with pathological hallmarks of PD, including mitochondrial dysfunction, dopaminergic vulnerability, and alpha-synuclein-related pathology, and highlight the link with cellular and systemic oxygen sensing. We describe cases suggesting that hypoxia may trigger Parkinsonian symptoms but also emphasize that the endogenous systems that protect from hypoxia can be harnessed to protect from PD. Finally, we provide examples of preclinical and clinical research substantiating this potential.
Gesehen am 21.06.2024